(3bUjOI TYQs - (3CMeO Hf YHO GdefYe Hf GdMjejs
(3ChdgG (B:s
(3eG eWdHG djS dj aj ZjQg CQH (B*** (3Edjc EdG dJbVj hCfJ GdWdH , heG WeMJ deQGA Ch deSJeY (B*** (3EdG deYfG Edi Ydjc jfJSHs
(3BNQgG (B:s
(3eG jfJgj fXQj efge Edi QJH (B*** (3aj GdMSf EdG hdGMJ ahbgG QJHs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdCOHs